Potential biotechnological properties of an exopolysaccharide produced by newly isolated Bacillus tequilensis-GM from spontaneously fermented goat milk. (May 2019) - Abid, Yousra; Azabou, Samia; Joulak, Ichrak; Casillo, Angela; Lanzetta, Rosa; Corsaro, Maria Michela; Gharsallaoui, Adem; Attia, Hamadi
Abstract: In the present work, an exopolysaccharide (EPS) was produced by a newly isolated Bacillus tequilensis -GM ropy strain. Results showed that EPS-GM was produced simultaneously with the growth phase and reached its maximum (2.9 g/L) when sucrose was used as carbon source. According to GC-MS and HPLC-SEC results, the recovered EPS-GM was composed by fructose, glucose, mannose, galactose, galactosamine and N -acetyl-glucosamine, with high molecular weight ranging between 1.8 and 2.5 × 10 6  Da. Different properties of EPS-GM were tested. Results showed that crude EPS-GM has several potential features, including high thermostability evaluated by DSC (with a melting point of 222 °C), good emulsifying properties and stability at both neutral and acidic pH, and high capacities to adsorb heavy metal ions (94.96% of Fe 2+, 97.66% of Zn 2+ and 98.24% of Cu 2+ ) making it promising to be used in different industrial fields. Highlights: EPS-GM was produced simultaneously with the growth phase of B. tequilensis -GM. EPS-GM exhibited high thermostability. EPS-GM showed good emulsifying properties at both neutral and acidic pH. EPS-GM was able to adsorb high levels of heavy metal ions.